2009
DOI: 10.1192/bjp.bp.108.053751
|View full text |Cite
|
Sign up to set email alerts
|

Selective drop-out in longitudinal studies and non-biased prediction of behaviour disorders

Abstract: BackgroundParticipant drop-out occurs in all longitudinal studies, and if systematic, may lead to selection biases and erroneous conclusions being drawn from a study.AimsWe investigated whether drop out in the Avon Longitudinal Study of Parents And Children (ALSPAC) was systematic or random, and if systematic, whether it had an impact on the prediction of disruptive behaviour disorders.MethodTeacher reports of disruptive behaviour among currently participating, previously participating and never participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

41
414
3
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 556 publications
(462 citation statements)
references
References 37 publications
41
414
3
4
Order By: Relevance
“…Although the prevalence of depressive disorder is low in early adolescence (Costello et al 2006;Shanahan et al 2011), the prevalence of DAWBA-assessed depression and anxiety diagnoses in 13-15 year olds has been shown to be respectively 2.5% and 5%, in a nationally representative UK sample (Ford et al 2003). These figures are higher than in this study, which could be explained by selective drop out: the ALSPAC participants who consistently participated were less likely to have a psychiatric diagnosis (Wolke et al 2009a). …”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Although the prevalence of depressive disorder is low in early adolescence (Costello et al 2006;Shanahan et al 2011), the prevalence of DAWBA-assessed depression and anxiety diagnoses in 13-15 year olds has been shown to be respectively 2.5% and 5%, in a nationally representative UK sample (Ford et al 2003). These figures are higher than in this study, which could be explained by selective drop out: the ALSPAC participants who consistently participated were less likely to have a psychiatric diagnosis (Wolke et al 2009a). …”
Section: Discussioncontrasting
confidence: 67%
“…Indeed power was limited for DSM-IV diagnoses. In contrast, the relationship between predictors and depression symptoms is unlikely to have been substantially altered by selective dropout processes as has been shown in simulations (Wolke et al 2009a), nevertheless it cannot be ruled out.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…As these predictors of attrition also predict child psychopathology, our sample is likely to under‐represent the most severely affected children. Of note, an ALSPAC cohort study (Wolke et al., 2009) has shown that attrition affects the prevalence of DSM‐IV disruptive behavior disorders (which includes ODD), however, associations between risks and outcomes remained present, although conservative of the likely true effects. Fifth, although the ALSPAC sample represents a broad spectrum of SES backgrounds, it includes relatively low rates of ethnic minorities.…”
Section: Discussionmentioning
confidence: 99%
“…51 "True" relationships between an exposure (i.e. role in bullying) and outcome (suicidal ideation or suicidal/self-injurious behavior) should be found irrespective of whether they are investigated in more, or less, advantaged sections of the population.…”
Section: Discussionmentioning
confidence: 99%